PENTINGNYA PENDIDIKAN ANAK USIA DINI DALAM MENGURANGI ANGKA ANAK PUTUS SEKOLAH DAN PERILAKU MENYIMPANG ANAK (Studi Kasus di Lingkungan Kornelis, Paroki Katedral Merauke) - Pranyoto, Yohanes Hendro (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2017)
This paper intends to describe the level of parental understanding in earlychildhood education in the family, describes parenting patterns and factorsthat lead to drop out rates and child deviant behavior. In this study theauthors used a qualitative approach and data were collected using interviewand observation techniques.The results of this study indicate that in general, parents realize the importanceof early childhood education but the awareness is not accompanied by theattention to the education of their children so that the pattern of care thatis formed is permissive parenting. The most dominant factor affecting earlychildhood education is environmental factors.Based on the results of this study, the author suggest to families to improve theparental control function of their childrenâs education process in formal school.In addition, parents need to supervise their childâs association so that childrendo not choose the wrong friends in associating. The social environment has asignificant impact on changes in childrenâs behavior, increasing the frequencyof delinquency or deviant behavior that increases the potential of children todrop out.